Factors impeding on the successful implementation of SDG 6 in Africa - Vyas-Doorgapersad, Shikha (Journal of Ecohumanism, 2025)
The infrastructure supporting water supplies will inevitably be under ongoing strain for several reasons, which the article attempts to examine. Therefore, practical steps must be taken to address the issues associated with water. Rapid urbanization, migration, and climate-related disasters in African nations create water concerns that need for tailored, strategic solutions. The article aims to explore the water infrastructure (focus) challenges in African context (locus). This may assist policymakers in identifying factors that may restrict the achievement of sustainable development goal (SDG) 6. The article uses a qualitative research approach to compile information. The data was collected using secondary sources hence performed document review of available published works. The findings explore various challenges linking to migration, population, climate change, etc. that implies pressure on water infrastructure. The article proposes the consideration of public private partnership arrangement to share the challenges and find solutions in a manner benefiting all stakeholders.